Employee Satisfaction and Competitive Advantage of Virtual Organisations in Lagos State, Nigeria - Omorodion Omoregbe; Joseph Azage (Faculty of Economics, Universitas Sriwijaya, 2022)
This research study investigated the impact of employee satisfaction on the competitive advantage of selected virtual organisations in Lagos State, Nigeria. Specifically, it assessed the relationship between individual virtual competencies, motivation, organisational identity, autonomy, the nature of the work and the competitive advantage of virtual organisations in Lagos State, Nigeria. The population of interest in this study covered all staff in selected virtual organisations in Lagos State, Nigeria. A total of 400 copies of questionnaire were distributed to and retrieved from the respondents. Stratified random sampling procedure was used in administering/distributing the copies of questionnaire to a selection of virtual organisations in Lagos State, Nigeria. The data is analysed using OLS regression. The study discovered that there is a significant positive relationship between individual virtual competencies, motivation, organisational identity, the nature of the work and competitive advantage while revealing that there is a positive and non-significant relationship between autonomy and the competitive advantage of virtual organisations in Lagos State, Nigeria. The study recommends that virtual organisations employ individuals that have the required skills and competencies needed to perform the various organisational tasks, motivate their employees intrinsically and extrinsically, possess a strong brand image, allow employees experience freedom to do their tasks and duties at their own pace and take cognisance of employees that work in dispersed locations with peculiar difficulties in those varied locations so that they will productive and contribute more to the competitive advantage of the virtual organisation.